HER2 testing in malignant effusions of metastatic gastric carcinoma: Is it feasible?. Issue 1 (3rd November 2014) - Wong, Daniel D.; de Boer, W. Bastiaan; Platten, Michael A.; Jo, Vickie Y.; Cibas, Edmund S.; Kumarasinghe, M. Priyanthi; Aisner, Dara; Hjerpe, Anders
<x xml:space="preserve">Abstract</x> HER2 testing on effusions of metastatic gastric carcinoma may provide a valuable alternative to testing on primary biopsies. This study assessed the feasibility of this method by immunohistochemistry (IHC) and silver in situ hybridization (SISH). Cell blocks from 46 effusions from metastatic gastric carcinoma were examined. IHC was scored using the modified criteria of Hofmann et al. An average of ≥6 signals per nucleus was considered amplification on SISH. Results were compared with histological specimens to assess HER2 status concordance. Cell blocks showed a poorly cohesive pattern in 30 (65%), aggregates in 7 (15%), and mixed pattern in 9 (20%). Seven (15%) showed an IHC 2+/3+ reaction with a membranous pattern, appearing more granular than in histology. Three (7%) showed HER2 amplification on SISH. In 18 cases (39%), HER2 status was compared with histological specimens, showing 100% concordance. Difficulties were encountered in distinguishing malignant cells from reactive mesothelial cells in 12 (26%). This study supports the feasibility of HER2 assessment on effusions. The incidence of HER2 positivity (7% with SISH+ and IHC 2+/3+) was lower than reported in histological samples. Further refinement and validation will enhance the use of this method in clinical practice and overcome difficulties encountered. Diagn. Cytopathol. 2015;43:80–85. © 2014 Wiley Periodicals, Inc.